Environmental contamination of lead in dairy farms in Narayangonj, Bangladesh - Aktar, Sharmin; Sarker, Yousuf Ali; Sachi, Sabbya; Ferdous, Jannatul; Noman, Zakaria Al; Mohiuddin, K M; Sikder, Mahmudul Hasan (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: In recent years, lead (Pb) has arisen as a foremost contaminant due to overpopulation, rapid industrialization, and expansion that could contaminate the human food chain. However, the correlation between the environmental contamination of Pb and its spatial transfer to the dairy products is still unmapped. In this paper, we intend to evaluate the concentration of environmental Pb and its spatial distribution in dairy feed and products in Narayangonj, a highly polluted district of Bangladesh. Materials and Methods: A total of 125 samples of soil, water, forage, and milk were collected from five upazilas (Narayangonj Sadar, Bondor, Rupgonj, Araihazar, and Sonargoan) of Narayangonj. The samples were digested by acid digestion, and Pb was detected by flame atomic absorption spectrophotometer and graphite furnace atomic absorption spectrometer. The bioconcentration factor of the samples was also calculated. Results: In this study, 25% of the soil, 20% of the water, 5% of the forage, and 2% of the milk samples contained Pb at a variable level. Among the environmental samples, the highest concentration (26–39 μg/kg) of Pb was detected in the soil, followed by in the water (0.023–0.059 μg/ kg) and forage (0.017–0.035 μg/kg). The contamination (0.041–0.068 μg/kg) in the milk, however, was lower than the soil but higher than the water and forage. The concentration of Pb in all the samples was within a safer limit. None of the forage samples was the potential bioaccumulator. Conclusion: Although no linear correlation was established between the environmental samples, forage, and milk, the study identifies the potentials of the spatial distribution of Pb from the environment to the dairy feed and products. Therefore, feasible procedures should be adapted to cease the residue to the human food chain. J. Adv. Vet. Anim. Res., 7(4): 621-625, Dec 2020 http://doi.org/10.5455/javar.2020.g460